Topology Optimization and Impact Analysis of Crowd Reducer Box of Large Mining Electric Excavator - Hou Geng; Zhang Yinghui; Ge Zailin; Ru Xuebin (Jixie chuandong, 2018)
In order to reduce the material consumption of crowd reducer box of large mine excavator and to realize the box light weight,topology optimization of the upper box is carried out. Based on finite element analysis about stress of electric excavator crowd reducer box,by using the variable density method,the mass of upper box is taken as the optimization objective,and the maximum stress,the wall thickness of box and the remaining percentage are taken as the topology constraint conditions,according to the force transmission path,topology optimization of crowd reducer upper box of mining electric excavator is achieved. The finite element method is used to analyze the maximum stress of the box before and after optimization. According to the standard ISO 6336: 2006 and the standard ISO/TS 16281: 2008,the gear stress（ including the contact stress of teeth surface and the bending stress of teeth root） and bearing life of before and after optimization are analyzed respectively. The optimization results show that the topology optimization of the reducer upper box has a minimal influence on the stress of the box and the fatigue life of the bearing. Although the optimization makes the gear stress increase slightly,the gear still meets the requirement of strength.